THE INFLUENCE OF TELEWORKING, WORK STRESS, AND WORKLOAD TOWARD WORK-LIFE BALANCE DURING WFH (CASE STUDY IN SOUTH JAKARTA) - Meytri Yuni Ekaristy; Liswandi Liswandi (Sekolah Tinggi Ilmu Ekonimi IPWI Jakarta, 2022)
The COVID-19 outbreak has forced employees to work from home as one of the government's actions to minimize the spread of the coronavirus. However, for some employees, implementing WFH is a challenge for them. In this study, there are Teleworking, Work Stress, Workload, and Work-Life Balance as variables to be examined because researchers want to know the influence of Teleworking on Work-Life Balance, Work Stress on Work-Life Balance, and Workload on Work-Life. Balance, as well as the simultaneous influence of Teleworking, Work Stress, and Workload on Work-Life Balance. The method used in this study is quantitative and statistical analysis was carried out using SPSS 28.1. Data from 179 workers in the South Jakarta area who had or are currently working from home were obtained through questionnaires. The results show that all variables have a significant influence on work-life balance. So, it is important to maintain the work-life balance of all workers and influencing factors for the benefit of all parties. Keywords: teleworking, work stress, workload, work-life balance